Euler Type Half-Linear Differential Equation with Periodic Coefficients - Ondřej Došlý; Hana Funková (Abstract and Applied Analysis)
We investigate oscillatory properties of the perturbed half-linear Euler differential equation. We show that the results of the recent paper by O. Došlý and H. Funková (2012) remain to hold when constants in perturbation terms are replaced by periodic functions.